4. The Feldenkrais Method in the Puppeteer's Training from the Perspective of Nicolas Gousseff's Handheld Puppets Workshops - Ciofu Anca-Mihaela (Sciendo, 2018)
Although the Feldenkrais method is quite well-known and used in relation to dance, music, and acting, it is rather uncommon to associate it with animation theatre. The puppeteer's art is a profession that requires motor skills and sustained physical effort, which demands that the animating actor has an extended consciousness of oneself and of the space. Therefore, the Feldenkrais method can be a useful instrument in the puppeteer's education and training, as the placing of the body in a relaxed stance, one which helps in the management of pain and effort, facilitates the conscious and creative learning of animation techniques, with an emphasis on the coordination and fluidity of movement. These are learning principles of the art of animation that are successfully used by Nicolas Gousseff, an artist that was formed at ESNAM (École Supérieure Nationale des Arts de la Marionnette de la Charleville-Mézières), and who has specialized in handheld puppets and using the actor's body as a performative space for this type of animation.